Disease activity trajectories from childhood to adulthood in the population-based Nordic juvenile idiopathic arthritis cohort - Kristiina Aalto; Anders Fasth; Troels Herlin; Marite Rygg; Ellen Berit Nordal; LILLEMOR BERNTSON; Mia Glerup; Veronika Rypdal; Martin Rypdal; Ellen Arnstad; Charlotte Myrup; Suvi Peltoniemi (RMD Open)
Objectives To identify long-term disease activity trajectories from childhood to adulthood by using the clinical Juvenile Arthritis Disease Activity Score (cJADAS10) in juvenile idiopathic arthritis (JIA). Second, to evaluate the contribution of the cJADAS10 components and explore characteristics associated with active disease at the 18-year follow-up.Methods Patients with onset of JIA in 1997–2000 were followed for 18 years in the population-based Nordic JIA cohort. We used a discrete mixture model for longitudinal clustering of the cJADAS10 and its components. We assessed factors potentially associated with higher scores on the patient’s global assessment of well-being (PaGA) by hierarchical clustering and correlation analysis.Results Four disease activity trajectories were identified based on the cJADAS10 components among 427 patients. In trajectory-group 2, the PaGA and the physician’s global assessment of disease activity (PhGA) increased significantly during the course, but not the active joint count. The increase in the PaGA was significantly higher than the increases in the PhGA and the active joint count (p<0.0001). A similar pattern was found among all the patients with active disease in the total cohort. Patients with higher PaGA scores had unfavourable scores on several other patient-reported outcomes.Conclusions We have identified groups of patients based on long-term disease activity trajectories. In our study the PaGA was the most important driver of disease activity into adulthood assessed by cJADAS10. We need to better understand how our patients interpret global well-being and implement strategies to achieve inactive disease perceived both by the patient and the physician.